ANALISIS SISTEM PELAYANAN ASURANSI DANA PENSIUN PT TASPEN CABANG MEDAN DI SETDA PROVSU - Darwin Multa Nasution; Suci Wulandari Siregar (MANAJEMEN, 2025)
This research aims to analyze the pension fund insurance service system at the Regional Secretariat of North Sumatra Province (Setda Provsu) which is managed by PT TASPEN Medan Branch. The main focus of this research is to determine the extent of service quality, procedures and obstacles in the process of managing pension fund claims. The research method used is a descriptive method with a qualitative approach, through interviews and direct observation of employees and beneficiaries. The research results show that PT TASPEN has implemented several digital-based service innovations, such as the Taspen Mobile application, but there are still obstacles in disseminating information and understanding procedures by participants. In addition, it was found that claims processing times were sometimes delayed due to insufficient completeness of the files. This research's recommendations include increasing outreach to pension fund participants and optimizing technology-based service systems in order to increase satisfaction and service efficiency